Performance of Angus, Devon and crossbred Angus x Devon x Nelore young steers in feedlot - Gottschall, Carlos Santos; Canellas, Leonardo Canali; Ferreira, Eduardo Tonet; Bittencourt, Hélio Radke (Semina: Ciências Agrárias, 2007)
The study was based on data from 129 beef steers from three genetic groups: Angus (AN, n=45), Devon (DV, n=35) and Crossbred Angus x Devon x Nelore (CB, n=49), with an average beginning weight (ABW) of 277.60, 278.00 and 295.53 kg, respectively. Those animals were in a feedlot with 11 months of age, to be slaughtered at 14 months. The parameters analyzed were: days on feed (DF), average weight gain (AWG), total weight gain (TWG), average slaughter weight (SW), average carcass weight (CW), average carcass yield (CY) and carcass classification (CC). The analysis were done using the ABW as a covariate because of these variable in the group CB were higher (p < 0,01) than AN and DV groups. The variables AWG, DF and CC did not show difference among the groups (p > 0.05). CB animals got a higher SW (375.04 kg) than DV (359.40) (p < 0.05), while AN (356.31 kg) did not differ from DV and CB (p > 0.05). The CW (p < 0.05) and CY (p < 0.01) were higher to CB (191.12 kg and 50.99%) than AN (179.81 kg and 49.73%) and DV (177.23 kg and 49.41%), respectively. Angus and Devon beef steers had similar results in all variables analyzed. Crossbred animals presented greater carcass weight and carcass yield than the others groups.